Bedtime extended release cornstarch improves biochemical profile and sleep quality for patients with glycogen storage disease type Ia - Rai‐Hseng Hsu; Hui‐An Chen; Yin‐Hsiu Chien; Wuh‐Liang Hwu; Ju‐Li Lin; Hui‐Ling Weng; Yi‐Ting Lin; Yu‐Ching Lin; Ni‐Chung Lee (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Patients with glycogen storage disease type Ia (GSDIa) are prone to hypoglycemia. Uncooked cornstarch (CS) is the treatment, but maintaining nighttime blood glucose levels is still difficult. Methods The study enrolled patients with GSDIa to investigate the benefits of bedtime extended release CS (ER‐CS, Glycosade®) versus regular CS. The daytime CS schedule was not altered. A 7‐day continuous glucose monitoring (CGM) was performed at the baseline and 12 weeks after using ER‐CS. Biochemical profile, sleep quality (Pittsburgh Sleep Quality Index, PSQI), and quality of life (SF‐36 questionnaire) were measured at the baseline and 24 weeks after using ER‐CS. Results Nine patients (9 to 33 years of age) were enrolled. Compared with the baseline (80.0 ± 6.33 mg/dL), the 12‐week evaluations revealed higher mean morning glucose levels (86.5 ± 8.26 mg/dL, p = 0.015). Twenty‐four weeks after the use of bedtime ER‐CS, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels both decreased (from 69.3 ± 77.8 to 41.1 ± 40.4 U/L and from 78.8 ± 99.6 to 37.8 ± 28.81 U/L, respectively, p = 0.013 for both analyses), and sleep and fasting time both elongated (from 7.8 ± 0.87 to 8.6 ± 1.02 h and from 6.5 ± 1.22 to 7.6 ± 1.02 h, respectively, p = 0.011 for both analyses). The mean PSQI score in the five adult patients decreased significantly (from 5.8 ± 1.29 to 3.0 ± 1.71, p = 0.042). Conclusion This study provides evidence of clinically meaningful improvements by shifting only bedtime regular CS to ER‐CS in patients with GSDIa. As ER‐CS is considerably more expensive than regular CS, this approach presents a cost‐effective alternative.